ANALISIS SPASIAL DAN FAKTOR RISIKO TB PARU DI PUSKESMAS KABUPATEN BANYUMAS TAHUN 2013 - , Andri Muhammad, Prof. dr. Hari Kusnanto Josef SU., Dr.PH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Pulmonary TB is still a problem in Banyumas. Cases in Puskesmas, in 2012, 716 cases, the most cases in District of Kembaran. Contact with previous TB patient, dwelling density, poverty, smoking status, and diabetes mellitus as risk of pulmonary TB. Spatial analysis such as buffers, clusters, and diffusion describe patterns of TB transmission. Objectives: to know relationships contacts with previous TB patient, dwelling density, poverty, smoking status, and diabetes mellitus against pulmonary TB, and the pattern of spatially TB distribution. Methods: study design is, spatial and case-control study, subject 10 -> 64 years. Cases are smear-positive pulmonary TB, the fourth quarter of 2012 to the third quarter of 2013. Controls were patients who are not sick pulmonary TB. Samples were taken by purposive sampling, and do matching based age and gender, a sample size of 124 people. Data collection by questionnaires, and location coordinates by GPS (Global Positioning System). Analysis by logistic regression, using Stata version 10 while buffer and kernel density analysis by arcgis arview. Results: subjects aged 11-80 years old. Pulmonary TB associated with previous TB patients contacts (coworkers) (p = 0.046